PRAS40 is an integral regulatory component of erythropoietin mTOR signaling and cytoprotection. - Zhao Zhong Chong (Public Library of Science (PLoS), 2012)
Emerging strategies that center upon the mammalian target of rapamycin (mTOR) signaling for neurodegenerative disorders may bring effective treatment for a number of difficult disease entities. Here we show that erythropoietin (EPO), a novel agent for nervous system disorders, prevents apoptotic SH-SY5Y cell injury in an oxidative stress model of oxygen-glucose deprivation through phosphatidylinositol-3-kinase (PI 3-K)/protein kinase B (Akt) dependent activation of mTOR signaling and phosphorylation of the downstream pathways of p70 ribosomal S6 kinase (p70S6K), eukaryotic initiation factor 4E-binding protein 1 (4EBP1), and proline rich Akt substrate 40 kDa (PRAS40). PRAS40 is an important regulatory component either alone or in conjunction with EPO signal transduction that can determine cell survival through apoptotic caspase 3 activation. EPO and the PI 3-K/Akt pathways control cell survival and mTOR activity through the inhibitory post-translational phosphorylation of PRAS40 that leads to subcellular binding of PRAS40 to the cytoplasmic docking protein 14-3-3. However, modulation and phosphorylation of PRAS40 is independent of other protective pathways of EPO that involve extracellular signal related kinase (ERK 1/2) and signal transducer and activator of transcription (STAT5). Our studies highlight EPO and PRAS40 signaling in the mTOR pathway as potential therapeutic strategies for development against degenerative disorders that lead to cell demise.